Hak Kewarisan Anak Angkat Menurut Hukum Islam - Anton; Silva Eka Diani; Salsabila Saqina; Fikri Muhammad Latif; Rival Munawar; Muhamad Fakri Ramdan (PT. Penerbit Tiga Mutiara, 2024)
The presence of a child can be a link between couples. However, in fact, some married couples cannot have children, even though they really need children in their domestic life. So the effort to care for or hug a child then becomes an option to get a child even though he is not a natural child. The law states that the purpose of adopting a child is simply to improve the welfare of the child.This research aims to find out and examine Islamic legal regulations regarding the inheritance rights of adopted children. The position of children in Islamic law is still attributed to their biological guardians and not to their adoptive fathers. Moreover, in Islamic inheritance law, adopted children do not get inheritance privileges from the father who supports them, but the freedom of inheritance returns to the biological father of the child being cared for. Children raised in Islam can acquire property from their supportive father through a bequest course and then a mandatory will course. Since taking over, the children and their supportive father have been seen as having been a huge help in their respective lives. Therefore, as a substitute for the freedom inherited from the younger generation, Islamic law provides a way through mandatory gifts and wills.